Smart cities e empreendedorismo : diagnóstico da cidade de Aracaju e proposta de iniciativas inteligentes - Santos, Ricardo Tadeu Soares (2019)
This paper aims to diagnose the Smart Cities dimensions of the city of Aracaju. The conceptual model of Giffinger and Gudrun (2010) was used, focusing on the tripod Life, Governance and Economy. This is a descriptive study, divided into two parts (theoretical and practical), with qualitative and quantitative treatment.The diagnosis of the city (part 1) was performed according to Smart City concepts, as well as the opinion poll of the citizens with a self-administered electronic questionnaire (part 2), formulated from the compilation of smart initiatives. The statistical analysis of part 2 used the descriptive and inferential methods (IBM SPSS 20 and R-Studio 3.6.1 software). The results of part 1, regarding the Intelligent Life dimension, there was an 11.03 year increase in life expectancy in the last two decades, following the national trend. Aracaju has the 14th position among the other national capitals with the largest number of doctors (1.30 / 1000hab.); the lowest number of hospital beds (1.49 bed / 1000hab. for SUS); adding the public and private hospital beds, there are only 1.85 beds / 1000hab (by WHO, min. 3 to 5). Aracaju has had significant growth in access to education compared to the national average. The illiterate percentage is 8.8% (national average of 11.8%); 95.0% of the children (≤6 years) are enrolled; among individuals ≥25 yo, have completed high school 53.1% (national average of 35.8%) and have completed higher education 19.2% (national average of 11.3%). The proportion of children and youth attending or having completed learning cycles raises the state's HDI Education, however, over the past eight years, Aracaju has scored (4.7) below the INEP target (4.9). Regarding Intelligent Governance, GDP per capita increased 52.8% from 2010 (R$ 16,821.37) to 2016 (R$ 25,717.68), ranking 4th in GDP per capita in Sergipe. The average per capita income has grown little in the last three decades, from R$ 513.29 (in 1991) to R$ 2,811.00 (in 2017), however, it has 35.8% of residents with monthly income ≤ half minimum wage. The growth and development of the citizens does not match the average income per capita and the purchasing power of the citizen. Regarding Intelligent Economy, there were 15,064 companies operating in 2017 (44th position among the cities of the country). It is most relevant to the sectors: commerce, food, small manufacturing industries, inns and construction. MSEs have a relevant role in the municipal economy (evidenced in the tax regime). There are 16 startups registered in ABSTARTUPS; three northeastern cities are among the 10 national leaders (Salvador, Recife and Fortaleza, with 200, 186 and 158 startups). Regarding the questionnaire, 1526 citizens (65.1% female; 18 to 65 years; non-normal age distribution, concentrated between 20-40 yo) answered. Among the 12 initiatives, the valid percentage of respondents who understand their application in Aracaju as needed as soon as possible ranged from 75.2% (―educational integration between schools‖) to 93.6% (―efficient control of garbage collection‖ ). Overall opinion (Likert scale 1-5) was higher among young and female subjects (95% CI, p <0.05).